Solvent-Dependent Cytotoxicity of Peperomia pellucida Leaf Extracts Against MCF-7 Breast Cancer Cells - Arsianti, Ade; Pratama, Rafael Erlangga Bagas; Gill, Steven; Kristanty, Diyah (Indonesian Journal of Medical Chemistry and Bioinformatics, 2026)
Background: Breast cancer remains a major global health burden. Particularly in Indonesia, limitations of conventional chemotherapy, such as severe side effect, toxicity, and high cost, indicating the necessitate the development of alternative therapeutic agents. Peperomia pellucida, a medicinal plant rich in bioactive phytochemicals, has shown promising anticancer potential; however, its cytotoxic activity against MCF-7 breast cancer cells and the influence of solvent polarity remains underexplored. This study aimed to evaluate the cytotoxic effects of P. pellucida leaf extracts which are prepared using different polarity of solvents (ethanol, ethyl acetate, and n-hexane). Method: Dried leaf powder of P. pellucida was extracted via maceration, and the resulting extracts were tested against MCF-7 cells using the MTT assay. Cells were exposed to concentrations ranging from 3.125 µg/mL to 400 µg/mL, and cytotoxicity was expressed as IC₅₀ values derived from linear regression analysis. Results: The ethanol extract exhibited the the strongest cytotoxic activity (IC₅₀ = 10.68 µg/mL), followed by the ethyl acetate extract (IC50=17.81µg/mL), while the n-hexane extract showed weak activity (IC50 = 62.73 µg/mL). The superior activity of the ethanol extract is attributed to its broader phytochemical profile, including flavonoids, alkaloids, tannins, and triterpenoids, which may act synergistically to induce apoptosis and inhibit proliferation. Conclusion: P. pellucida demonstrates solvent-dependent cytotoxic activity, with ethanol extract showing the highest potential as a candidate for breast cancer therapy. Further studies are required to elucidate its molecular mechanisms.